Reconstructing the Meaning of Fiqh Learning through Accelerated and Quantum Learning in the Digital Generation - Irfan Musonif; Syifa Salsabila; Risa Naelatus Syifa; Donny Khoirul Azis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study addresses a critical gap in Islamic education by rethinking fiqh learning beyond its traditional normative-transmissive orientation toward a more meaningful and contextually grounded process. Employing a qualitative case study design, the research was conducted in a Grade 11 classroom at MA Raudlotut Tholibin Banjarnegara between January and February 2026. Data were generated through in-depth interviews, classroom observations, and document analysis, and analyzed using reflexive thematic analysis. The findings demonstrate a fundamental shift in fiqh learning from knowledge transmission to a process of experiential and socially mediated meaning construction. This transformation unfolds through a dynamic interplay of student engagement, pedagogical adaptation, and experiential learning practices, in which students actively negotiate meaning through interaction, reflection, and lived experience. Engagement extends beyond observable participation to include cognitive and reflective involvement, while adaptation emerges as an inherent dimension of the learning process rather than a transitional stage. Consequently, fiqh is no longer understood as a fixed body of normative knowledge but as a contextual and lived practice shaped by students’ everyday realities. The study offers a theoretical contribution by reconceptualizing fiqh learning as a process of socially mediated experiential meaning-making, thereby challenging dominant transmissive paradigms in Islamic education. Practically, it underscores the need for designing interactive and context-sensitive learning environments aligned with the characteristics of digital generation learners. Ultimately, this study positions fiqh learning as a transformative pedagogical space where knowledge is continuously constructed, negotiated, and lived.